2008
DOI: 10.1002/tt.51
|View full text |Cite
|
Sign up to set email alerts
|

Relative fatigue life estimation of cylindrical hollow rollers in general pure rolling contact

Abstract: Increasing the hollowness percentage from 20 to 60% increased the fl exibility of the roller, and better stress distribution was achieved, which resulted in improving the fatigue life. Although 80% of hollowness rollers have more fl exibility than 60% of hollowness rollers, the bending stresses (s b ) on the inner surface of the rollers tend to decrease the fatigue life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The present authors are indebted to an anonymous referee for signalling that the above result, according to which a hollow pin of inner radius half the outer radius behaves similar to a solid pin, is confirmed by analogous conclusions valid for hollow rollers employed in roller bearings [14,15].…”
Section: Design Chartssupporting
confidence: 73%
“…The present authors are indebted to an anonymous referee for signalling that the above result, according to which a hollow pin of inner radius half the outer radius behaves similar to a solid pin, is confirmed by analogous conclusions valid for hollow rollers employed in roller bearings [14,15].…”
Section: Design Chartssupporting
confidence: 73%
“…The thin wall of the rollers allows preloading, as opposed to cylindrical bearings with solid rollers. Preloading rollers on large bearings with hollow rollers increases radial stiffness and reduces vibrations [19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first mathematical treatment of the contact problem of ideally smooth elastic solid, presented by Hertz in 1882, significant progress has been made in the field of contact mechanics. Many researchers (Harris and Aaronson, 1967; Scott, 1976; Darji and Vakharia, 2008; Abu-Jadayil, 2008; Bhateja and Hahn, 1980; Zhao, 1998) have found that hollow rollers have longer fatigue life than solid rollers. Here, a new cylindrical roller design is proposed in which a small hollow cylinder is embedded into another hollow cylinder; the so-called roller is given a name as “layered cylindrical hollow roller”.…”
Section: Introductionmentioning
confidence: 99%